The Effect of Trust and Brand Image on Customer Retention with Customer Loyalty as Intervening Variables to Customers of Sharia Commercial Banks - Ricadonna, Nadia Adriane; Saifullah, Muhammad; Prasetyoningrum, Ari Kristin (Jurnal Keuangan dan Perbankan, 2021)
Sharia banking is currently facing a very competitive industry era. Customer retention is one of the phenomena confronted by Islamic banks in Indonesia. Therefore, the problem in this research is how to increase customer retention in the Islamic banking sector. This study also aims to test and analyze the effect of trust and brand image on customer retention with customer loyalty as an intervening variable. A total of 100 customer respondents who have saving accounts for more than five years at Sharia Bank filled out the questionnaire in this study. The collected data were processed using the Smart PLS program with measurements of the inner and outer model tests. The test results proved that trust, brand image, and customer loyalty positively and significantly affect customer retention in Islamic commercial banks. Meanwhile, indirect testing proved that the customer loyalty variable could mediate customer trust and retention variables. However, it is unable to mediate the brand image variables on customer retention. DOI : https://doi.org/10.26905/jkdp.v25i2.5145